Utilização do ensino por investigação como recurso para aprendizagem sobre vacinas profiláticas e suas funcionalidades - Ubirajara Arcanjo Marques Junior (2020)
The congruence between the education and health spheres is always very important for the improvement of people's living conditions, as it favors improvement and reduces the occurrence of mistakes. When health issues are worked on in the school universe, knowledge becomes practical, debatable and interpretive as is necessary for science. For education, health is a prominent field for the perception of reality and problematizing activities, especially for everyone. This work launched the theme “Vaccines” in an instigating way to high school biology students, correlating Epidemiology with Human Ecology, encouraging the knowledge of the dynamics of the functioning of vaccines and their prophylactic action, raising awareness and leading to concerns regarding the paradoxical social problem of availability of several vaccines by the public health system in return for the frequent hesitation in their use, stimulated by false news poured into virtual social networks that nourish fears and various anxieties capable of even causing anti-vaccine movements. Through a didactic sequence permeated by several actions such as filling out closed questionnaires for analysis, research and interpretation activities, building seminars and a simulated jury, students built knowledge and changed many of their previous conceptions for knowledge based on science. With this foundation, it was evident that the student was encouraged to safely lead the way in the dissemination of knowledge in his community. The sequence proved to be dynamic and easily applicable, being able to be adaptable to several other themes, with the possibility of surprising results, verifiable through the construction of speeches and recurring debates.